2024
DOI: 10.1111/jipb.13607
|View full text |Cite
|
Sign up to set email alerts
|

A centromere map based on super pan‐genome highlights the structure and function of rice centromeres

Yang Lv,
Congcong Liu,
Xiaoxia Li
et al.

Abstract: Rice (Oryza sativa) is a significant crop worldwide with a genome shaped by various evolutionary factors. Rice centromeres are crucial for chromosome segregation, and contain some unreported genes. Due to the diverse and complex centromere region, a comprehensive understanding of rice centromere structure and function at the population level is needed. We constructed a high‐quality centromere map based on the rice super pan‐genome consisting of a 251‐accession panel comprising both cultivated and wild species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…S8 ). Recently, researchers identified a centromeric gene, AGIS_Os12g018490 ( OsMAB ), using eQTL and haplotype analysis, which plays a role in regulating tiller number in rice [ 11 ]. Several studies have also reported transcriptional activity in centromeric regions in plants and other species [ 52–54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S8 ). Recently, researchers identified a centromeric gene, AGIS_Os12g018490 ( OsMAB ), using eQTL and haplotype analysis, which plays a role in regulating tiller number in rice [ 11 ]. Several studies have also reported transcriptional activity in centromeric regions in plants and other species [ 52–54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The length and distribution of satellite repeats are species-specific [ 7 ]. For instance, CentO satellite repeats consist mainly of 155- and 165-bp monomers, which have been identified throughout a super pan-genome in rice [ 11 ]. Additionally, the Arabidopsis pan-centromere was found to contain two satellite repeats, AthCEN178 (~178 bp, formerly known as CEN180) and AthCEN159 (159 bp, formerly known as CEN160), which are mainly monomers in Arabidopsis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation